Jig-less assembly for aerospace manufacture - Snelling, Peter D. (Cranfield University, 2000)
Due to the high level of investment required to compete successively in the global aerospace and automotive markets, these industries are forced to form partnerships wherever possible and thereby share their resources appropriately. This in turn has brought about the requirement to provide a standardized flexible design and manufacturing capability in which interchangability and compatibility may take place. Current assembly practices and associated tooling can be traced back to the earliest days of aircraft production and have become relatively expensive and inflexible in today’s environment. The final assembly stage has been recognized to be a key area which has the potential to offer substantial returns as well as play a major role in any change management process within the organisation. Assembly tooling, jigs and fixtures, are required to support and maintain positional accuracy of components during assembly. Traditional jigs and fixtures make up for the short comings at the product design and manufacturing phases and add significantly to the final product costs and reduce flexibility in the production process. Jig-Less Assembly Concept (JAC) has been defined and researched with the aim to integrate and optimize various tools and techniques with which to reduce or eliminate the assembly tooling currently in use. The outcome of the research presents a comprehensive critique of the processes involved in and pertaining to the assembly of typical airframe assemblies. The thesis forms a platform from which to move forward towards the embodiment of the concept of jig-less assembly. Particular attention is drawn from the research to the need for appropriate organisational and management strategies as well as technical innovation in the adoption of a jig-less approach to airframe assembly. Together with BAe Airbus and Military this collaborative research seeks to define the scope of JAC by identifying and evaluating the issues and constraints, to enable the development of supportive techniques in unison with best practice engineering within a robust and sustainable manufacturing system. This commercially focused R & D required liaison and working at all levels within a variety of industrial sites using live case studies at Filton and Chester.